Crumbling of Amatrice clock tower during 2016 Central Italy seismic sequence: Advanced numerical insights - Francesco Clementi; Gabriele Milani; Angela Ferrante; Marco Valente; Stefano Lenci (Fracture and Structural Integrity)
The dynamic behaviour and the seismic vulnerability of the ancient civic tower of Amatrice, dramatically damaged by the last shocks sequence of 2016 that occurred in Central Italy, have been studied in this paper by means of advanced 3D numerical analyses with the Discrete Element Method (DEM). Thus, a discontinuous approach has been used to assess the dynamic properties and the vulnerability of the masonry structure, through large deformations regulated by the Signorini’s law, concerning the impenetrability between the rigid bodies, and by the Coulomb’s law, regarding the dry-friction model. Afterward, different values have been assigned to the friction coefficient of the models and real seismic shocks have been applied in the nonlinear analyses. The major purpose of this study is to highlight that relevant data on the real structural behaviour of historical masonry can be provided through advanced numerical analyses. The comparison between the results of the numerical simulation and the survey of the existing crack pattern of the bell tower permitted to validate the approach used. Finally, from the results and conclusions of this case study, it is possible to affirm that the used methodology can be applied to a wide variety of historical masonry structure in Europe.